2015
DOI: 10.5812/ijp.2363
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Oxidative Status in Serum and Breast Milk of Mothers Giving Birth Prematurely and at Full-Term

Abstract: Background:Burning fat and carbohydrates to provide energy in biological systems causes the formation of free oxygen species.Objectives:This study aimed to evaluate the oxidative status of serum and breast milk of mothers giving birth prematurely and at full-term.Materials and Methods:The study comprised 50 mothers who gave birth at full-term at more than 38 weeks and 43 mothers who gave birth pre-term at below 32 weeks. On the postnatal 5th day, samples of the mother’s milk and serum were taken and stored at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Similar results to ours were presented by Abuhandan et al [23], in which the TAS (total antioxidant status measured in μmol H2O2) of premature mothers' milk was also higher and was 0.21±0.03 compared with milk of mothers giving birth at a time (0.18±0.02) (22). Paduraru et al [24] did not show statistical significance between samples in total antioxidant status tested by the ABTS method in breast milk samples in similar test groups [24].…”
Section: Plos Onesupporting
confidence: 89%
See 1 more Smart Citation
“…Similar results to ours were presented by Abuhandan et al [23], in which the TAS (total antioxidant status measured in μmol H2O2) of premature mothers' milk was also higher and was 0.21±0.03 compared with milk of mothers giving birth at a time (0.18±0.02) (22). Paduraru et al [24] did not show statistical significance between samples in total antioxidant status tested by the ABTS method in breast milk samples in similar test groups [24].…”
Section: Plos Onesupporting
confidence: 89%
“…The discrepancy in results may be due to maternal factors, supplementation, perinatal factors, and eating habits of the nursing mother [25]. Scientists believe that the reduction of antioxidant levels in breast milk may be affected by stress, long hospitalization and mother's health [23,24,27].…”
Section: Plos Onementioning
confidence: 99%
“…21 Similarly, Abuhandan et al found higher TAC and TOS in preterm BM compared with term BM, but OSI was not found to be different between the groups. 31 In contrast, Quiles at al reported lower coenzyme Q, TAC, and α and γ tocopherol levels in colostrum and transitional milk of preterm newborns compared with term newborns. These levels were measured as close to identical in mature milk.…”
Section: Discussionmentioning
confidence: 93%
“…20 Abuhandan et al found that the oxidants and antioxidants in the milk of mothers of premature infants were significantly higher than those of full-term birth mothers. 21 Although the study groups enrolled similar number of subjects, the prematurity focused on 30e32 weeks' gestation, and the method used differed in terms of technique (Erel method) and units, so absolute values cannot be compared with ours. Moreover, the samples were collected on day 5 and preserved for an unspecified interval of time at À80 C, so comparison with our data would be inappropriate.…”
Section: Discussionmentioning
confidence: 99%